Optimization of local heating for a spherical shell made of titanium alloy BT-23 - Budz, S.F.; Astashkin, W.I.; Budz, I.S.; Chupyk, I.I. (Archives of Mechanics, 1998)
The problem of optimization of local heating for a spherical shell made of titanium alloy BT-23 in order to reduce maximal transient or residual stresses is posed and solved. The effect of the volume changes occurring during phase transition is taken into account. The minimum of the transient or residual stresses is adopted as an optimization criterion for determination of optimal temperature fields.